2019
DOI: 10.1042/bsr20181722
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-H19 promotes hepatic lipogenesis by directly regulating miR-130a/PPARγ axis in non-alcoholic fatty liver disease

Abstract: Background: As one of the most common liver disorders worldwide, non-alcoholic fatty liver disease (NAFLD) begins with the abnormal accumulation of triglyceride (TG) in the liver. Long non-coding RNA-H19 was reported to modulate hepatic metabolic homeostasis in NAFLD. However, its molecular mechanism of NAFLD was not fully clear. Methods: In vitro and in vivo models of NAFLD were established by free fatty acid (FFA) treatment of hepatocytes and high-fat feeding mice, respectively. Hematoxylin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 39 publications
(46 reference statements)
2
56
0
Order By: Relevance
“…C, Paraffin sections were further subjected to IHC staining with antibodies against mTOR, p-mTOR, LIPIN1, SREBP and MLXIPL. 56 Moreover, a recent study suggests that H19 may serve as a lipid sensor by synergizing with the RNA-binding polypyrimidine tract-binding protein 1 (PTBP1) to modulate hepatic metabolic homeostasis because deletion of H19 or knockdown of PTBP1 abolished high-fat and high-sucrose diet-induced steatosis. Representative images are shown while representative positive stains are indicated by arrows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C, Paraffin sections were further subjected to IHC staining with antibodies against mTOR, p-mTOR, LIPIN1, SREBP and MLXIPL. 56 Moreover, a recent study suggests that H19 may serve as a lipid sensor by synergizing with the RNA-binding polypyrimidine tract-binding protein 1 (PTBP1) to modulate hepatic metabolic homeostasis because deletion of H19 or knockdown of PTBP1 abolished high-fat and high-sucrose diet-induced steatosis. Representative images are shown while representative positive stains are indicated by arrows.…”
Section: Discussionmentioning
confidence: 99%
“…55 Consistent with our findings, H19 was shown to promote hepatic lipogenesis by regulating miR-130a/PPARγ axis in NAFLD animal model. 56 Moreover, a recent study suggests that H19 may serve as a lipid sensor by synergizing with the RNA-binding polypyrimidine tract-binding protein 1 (PTBP1) to modulate hepatic metabolic homeostasis because deletion of H19 or knockdown of PTBP1 abolished high-fat and high-sucrose diet-induced steatosis. 57 Nonetheless, it is conceivable that H19 may regulate hepatic lipid homeostasis through diverse mechanisms, especially implicating the PI3K/AKT/mTOR signalling axis.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting findings may possibly be explained by the fact that each study was based on a different in vivo model. Liu et al [43] observed H19 up-regulation, Srebp-1c, Acc1, Scd1, Fasn and Pparγ, increased expression in a model of NAFLD. This study was also conducted based on HFD mice model, so it is possible that H19 expression varies between different models, especially since lncRNA expression patterns are tissue-and state-specific.…”
Section: Long-non-coding Rna H19mentioning
confidence: 97%
“…H19 as well as genes that are involved in hepatic lipogenesis are upregulated in mice fed with high fat diet. 39,40 H19 directly downregulates the expression of miR-130a which in turn inhibits the expression of peroxisome proliferator-activated receptor γ level in the liver. 39 It also promotes steatosis by regulating transcription factor MLX-interacting protein-like (MLXIPL) or carbohydrateresponsive element-binding protein.…”
Section: Lncrna H19mentioning
confidence: 99%
“…39,40 H19 directly downregulates the expression of miR-130a which in turn inhibits the expression of peroxisome proliferator-activated receptor γ level in the liver. 39 It also promotes steatosis by regulating transcription factor MLX-interacting protein-like (MLXIPL) or carbohydrateresponsive element-binding protein. 40 H19 also serves as a lipid sensor by synergizing with RNA-binding protein, polypyrimidine tract-binding protein 1 (PTBP1), to modulate hepatic metabolic homeostasis.…”
Section: Lncrna H19mentioning
confidence: 99%